2020
DOI: 10.3390/molecules25153509
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Inhibition of Protein–Protein Interactions (PPIs) in STAT3: Insights into a New Class of Benzothiadiazole Derivatives

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a validated anticancer target due to the relationship between its constitutive activation and malignant tumors. Through a virtual screening approach on the STAT3-SH2 domain, 5,6-dimethyl-1H,3H-2,1,3-benzothiadiazole-2,2-dioxide (1) was identified as a potential STAT3 inhibitor. Some benzothiadiazole derivatives were synthesized by employing a versatile methodology, and they were tested by an AlphaScreen-based assay. Among them, benzosulfamide 1 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This online software also calculates whether the test sample is a pan-assay interference compound (PAIN). Similar filters are available also through the SmartsFilter [http://pasilla.health.unm.edu/tomcat/biocomp/smartsfilter] and Zinc15 Patterns [https://zinc15.docking.org/patterns/home/] services [39]. Overall, these approaches indicated that 1 and 2 exhibit desirable characteristics in terms of druggability and safety; moreover, the compounds successfully passed all the PAINS filters of the employed programs.…”
Section: Computational Studiesmentioning
confidence: 97%
“…This online software also calculates whether the test sample is a pan-assay interference compound (PAIN). Similar filters are available also through the SmartsFilter [http://pasilla.health.unm.edu/tomcat/biocomp/smartsfilter] and Zinc15 Patterns [https://zinc15.docking.org/patterns/home/] services [39]. Overall, these approaches indicated that 1 and 2 exhibit desirable characteristics in terms of druggability and safety; moreover, the compounds successfully passed all the PAINS filters of the employed programs.…”
Section: Computational Studiesmentioning
confidence: 97%